Studi Literatur: Pengaruh Self Assessment System Terhadap Penerimaan Pajak Penghasilan (PPH) - Riesta Auranissa; Muhammad Sidqy Arroyan Gunawan (Publikasi Indonesia, 2025)
The self-assessment system is a tax collection method that gives taxpayers the authority to independently determine the amount of tax they must pay each year based on applicable tax rules and regulations. This system's procedures provide taxpayers with the flexibility to independently fulfill their tax obligations, from calculating, recording, paying, and reporting their taxes. It is hoped that the implementation of the self-assessment system will positively contribute to increased income tax (PPh) revenue, thereby increasing state revenue. PPh itself is a type of tax imposed on taxpayers on the income, earnings, or receipts they receive within a tax year. Income tax is one of the largest contributors to state tax revenue. Given Indonesia's increasing population from year to year, the government expects revenue from this sector to continue to increase, both in terms of payments and reporting. This study aims to analyze the impact of the self-assessment system on PPh revenue. This study is based on a literature study that reviews the results of previous research related to the influence of the self-assessment system on income tax revenue, by referring to national and international scientific journals published in the period 2015 to 2025, through databases such as Neliti.com, Semantic Scholar, and Google Scholar.